The effects of energy density on the mechanical properties of SS316L produced by selective laser melting / Nur Aqilah Derahman - Nur Aqilah, Derahman (2018)
Selective laser melting (SLM) is an additive manufacturing (AM) method of fabricating different types of complex components using a layer-by-layer approach. The parts are produced directly from 3D computer-aided design (CAD) data by melting the powdered material layer-by-layer assisted by laser power. In this work, an experimental investigation was conducted into the SLM method process parameters using stainless steel 316L powder. The energy density which are the influence of laser power, scanning speed and hatching distance on the physic-mechanical properties such as surface roughness, dimensional accuracy, tensile strength, and hardness of the manufactured parts were investigated. The design of experiments was conducted using Taguchi’s L16 orthogonal array. Furthermore, statistical analysis with signal-to-noise response and analysis of variance were applied to obtain the optimal SLM parameter combinations. The experimental results indicated that laser power has the greatest effect on surface roughness, dimensional accuracy and hardness. However, scanning speed exhibited the greatest influence on the tensile strength of manufactured parts, followed by laser power and hatching distance. Next, the optimal parameters obtained were used in regression analysis to predict the mechanical properties. Subsequently, a confirmation experiment was carried out by using the optimal parameters determined. The confirmation experiment results were then compared with the predicted values during experiment validation. Lastly, the shot peening technique was used to improve the quality of the manufactured parts. Based on the results, shot peening improved the quality of the manufactured parts by about 33.28% for surface roughness, 58.33% for dimensional accuracy and 34.24% for hardness.